A scintillating nanoplatform with upconversion function for the synergy of radiation and photodynamic therapies for deep tumors. Issue 2 (15th December 2021) - Feng, Yansong; Liu, Xiaomeng; Li, Qiqing; Mei, Shilin; Wu, Kefan; Yuan, Jun; Tu, Langping; Que, Ivo; Tamburini, Filippo; Baldazzi, Fabio; Chan, Alan; Cruz, Luis J.; et al.
Abstract : Nanoplatforms consisting of an upconversion nanocore and an outermost X-ray active shell for PDT enable photoswitchable UCL imaging and RT&X-PDT. Abstract : Collaborative therapy is regarded as an effective approach in increasing the therapeutic efficacy of cancer. In this work, we have proposed and validated the concept of upconversion lumienscence image guided synergy of photodynamic therapy (PDT) and radiotherapy (RT) for deep cancer, via a specially designed nanoplatform integrating near infrared (NIR) light activated luminescence upconversion and X-ray induced scintillation. Upon NIR light irradiation, the nanoplatform emits highly monochromatic red light solely for imaging the targeted cancer cells without triggering therapy; however, when the irradiation turns to a low dose of X-rays, scintillation will occur which induces effectively the PDT destroying the cancer cells together with X-ray induced RT. The novel theranostic nanoplatform is constructed in such a way that the interactions between the upconversion core and the outmost scintillating shell are blocked effectively by an inert layer between them. This structural design not only enables a nearly perfect excitation energy delivery (∼100% at a spectral overlapping wavelength of ∼540 nm) from the outermost scintellating layer to the surface-anchored photosensitizers and so a maximum yield of radical oxygen species, but also achieves a strong NIR induced upconversion luminescence for imaging. Since PDT and RT attack different parts of a cancer cell, this synergy is more effective in destroying cancer than a single therapy, resulting in the reduction of the X-ray irradiation dosage. As a proof of principle, the theranostic effect is validated by in vitro and in vivo experiments, exhibiting the great potential of this sort of nanoplatform in deep cancer treatment.